2008
DOI: 10.1534/genetics.108.087882
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analyses of Human Single- and Multilocus Tandem Repeats

Abstract: Using the compiled human genome sequence, we systematically cataloged all tandem repeats with periods between 20 and 2000 bp and defined two subsets whose consensus sequences were found at either single-locus tandem repeats (slTRs) or multilocus tandem repeats (mlTRs). Parameters compiled for these subsets provide insights into mechanisms underlying the creation and evolution of tandem repeats. Both subsets of tandem repeats are nonrandomly distributed in the genome, being found at higher frequency at many but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Furthermore, hybridization of EPSPS probes at distal ends of homologous chromosomes of K. scoparia (Fig. 1) also suggests that an increase in EPSPS copies in GR K. scoparia may have occurred as a result of unequal crossover, as the gene duplication via unequal crossover most likely occurs at the telomere region of chromosomes (Royle et al, 1988;Amarger et al, 1998;Ames et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, hybridization of EPSPS probes at distal ends of homologous chromosomes of K. scoparia (Fig. 1) also suggests that an increase in EPSPS copies in GR K. scoparia may have occurred as a result of unequal crossover, as the gene duplication via unequal crossover most likely occurs at the telomere region of chromosomes (Royle et al, 1988;Amarger et al, 1998;Ames et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…This can be explained by the following statements. Genomes of reptiles are estimated to consist of about 30-50% repeats, birds have been estimated to consist of 15-20% of repeats [40,41], Mus musculus of 26.1% [42,43], and 44.9% of human genome were occupied by repeats [44,45]. While SSR tracts make up 2.4% of the E. coli genome [46], significantly less than vertebrates'.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of EPSPS copies at the distal ends of homologous chromosomes 39 suggested that duplication of the EPSPS gene in K. scoparia may have occurred as a result of unequal crossing over, because such events are known to be most likely to occur in the telomeric region of chromosomes. 55 Importantly, a positive correlation between EPSPS gene copies and expression at the transcription and protein levels, 44,45 and continuous variation in EPSPS copies with glyphosate selection, 39 suggest that the EPSPS copy number in K. scoparia increases through an adaptive process because some duplicated genes confer an immediate adaptive advantage. 26 Recently using single-copy FISH, we demonstrated that in A. tuberculatus the EPSPS gene is located in the pericentromeric region of one pair of chromosomes.…”
Section: Chloris Truncatamentioning
confidence: 99%